Community-based psychosocial rehabilitation model for people with schizophrenia - Arif Gunawan; Annas Adimara; Ayu Tsalis Saputri; Azalika Kansa Namira; Bela Auliya Puspita Ningrum; Era Catur Prasetya (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2023)
Schizophrenia is a mental disorder that triggers the occurrence of impaired function in the human brain, behavior, cognitive, and emotional functions. This disorder has become a problem in the study of mental health, which must be treated comprehensively by using empirical treatment combined with rehabilitation. Hopefully, increasing the maximum level of healing and reducing recurrence rates can improve social function and quality of life. Thus, this review aims to narrate the model and effective community-based psychosocial rehabilitation center. The articles of the studies published from 2017-2021 were collected and analyzed in this literature review. The keywords used were community-based rehabilitation for schizophrenia. The results show that in addition to pharmacological therapy, six community-based psychosocial non-pharmacological therapy methods are considered effective for intervention in patients with schizophrenia. The methods are club methods in elderly schizophrenic patients, community-based methods, direct patient decision-making methods, case and club management methods, psychoeducational and social skills methods, and community care unit methods. All of the above methods analyzed showed significant effectiveness in community-based psychosocial rehabilitation treatment in developing countries.